Analisis Keterampilan Mengajar Pendidikan Agama Islam Guru Raudhatul Athfal - Hanum, Latifah (AUD Cendekia: Journal of Islamic Early Childhood Education, 2021)
This study aims to analyze the teaching skills of Islamic religious education by prospective teachers raudhatul athfal. With the focus of the study on two things, namely: (1) Aspects of skills, (2) learning materials, and (3) teaching problems. This research was conducted at the Early Childhood Islamic Education Study Program, STAI Sumatra, Medan. This study uses a case study-based qualitative research method. With the research subjects are students of PIAUD STAI Sumatra Medan study program. To obtain research data, three techniques were used, namely observation, interviews, and documentation. The results showed that there were four main aspects of teaching skills, namely opening lessons, questioning skills, explaining skills, and concluding and closing lessons. Islamic Eduation learning materials in early childhood are not the same at elementary and middle ages, at this age the material tends to introduce Islam through a play atmosphere. The teaching problem that is often experienced by Teacher Raudhatul Athfal is the inability to package abstract Islamic Education material into real material that can be accepted according to their early age. Another problem is the cultivation of morality which tends not to be supported by the conditions of the family environment.